Effect of Surfactant Tween 80 (Polyoxyethylene Sorbitan Mono Oleate) Addition on Viscosity and Activation Energy on Making Asphalt Emulsion - Wirjosentono, Basuki (Talenta Publisher, 2020)
Asphalt emulsion is a mixture of asphalt (55% - 65%), water (35% - 45%) and emulsifier material (1% - 2%). This research studied the effect of adding surfactant tween 80 (polyoxyethylene sorbitan mono-oleate) on the viscosity and activation energy. The research data was obtained by mixing asphalt, surfactant tween 80, and water and then heated at a certain temperature and viscosity values were measured using a Brookfield Viscosimetre at 500 rpm. The results show that the viscosity and the activation energy increase with the addition of surfactant tween 80: Î· = -49,82380 cp end Ea = 9,18452154 kJ/mol